Epidemiology of burn injuries in the East Mediterranean Region: a systematic review - Kendrick Denise; Othman Nasih (BMC, 2010)
Abstract Background Burn injuries remain one of the leading causes of injury morbidity and mortality in the World Health Organization's East Mediterranean Region. To provide an overview on the epidemiology of burn injuries in this region, a systematic review was undertaken. Methods Medline, Embase and CINAHL were searched for publications on burns in this region published between 01/01/1997 and 16/4/2007. Data were extracted to a standard spreadsheet and synthesised using a narrative synthesis. No attempt has been made to quantitatively synthesise the data due to the large degree of clinical heterogeneity between study populations. Results Seventy one studies were included in the review, from 12 countries. Burn injuries were found to be one of the leading causes of injury morbidity and mortality. The reported incidence of burns ranged from 112 to 518 per 100,000 per year. Burn victims were more frequently young and approximately one third of the victims were children aged 0-5 years. Hospital mortality ranged from 5 to 37%, but was commonly above 20%. Intentional self-harm burns particularly involving women were common in some countries of the region and were associated with a very high mortality of up to 79%. Conclusion Burn injuries remain an important public health issue in the East Mediterranean Region therefore further research is required to investigate the problem and assess the effectiveness of intervention programmes.